Pentecostalism and migration: A contextual study of the migrant Ghanaian Classical Pentecostal churches in South Africa - White, Peter (HTS teologiese studies, 2021)
Pentecostal phenomenon from history has always moved with migration. Reading Acts 1:8, Jesus linked the baptism of the Holy Spirit with the migration of his disciples and the gospel from Jerusalem to Judea and Samaria and to the end of the earth. Migration has become a worldwide, multi-directional phenomenon which is reshaping the Christian landscape. In this light, the article discussed Pentecostalism and migration by using two Ghanaian Classical Pentecostal churches in South Africa as a case study. The article looked at their history, leadership development, transfer of missionaries from Ghana and its implications, their concept of contextualisation as well as some of their impact in South Africa. The article submits that it is time for both churches to start thinking of decolonising their foreign mission churches by helping them have autonomous status.Contribution: The article contributes to the on-going body of knowledge and research on migration with special emphasis on African classical Pentecostalism and migration. The study used Ghanaian Classical Pentecostal Churches in South Africa as a case study.